Women, History, and Information and Communications Technologies - Conrad, Margaret; Mullally, Sasha (Atlantis, 2010)
While women are attending universities in such large numbers that serious consideration is being given to affirmative action for men, the number of women enrolling in information and communications technologies (ICTs) programs seems to have stalled and even declined over the last three decades. This paper explores the larger context of women's engagement in the new media and surveys the landscape of women's involvement in digital history initiatives in Canada.